An Investigation of Students' Problems in Learning English of The Seventh Grade of SMP Muhammadiyah 2 Godean - FIRSTA MEYNA LARASATI (Universitas Ahmad Dahlan, 2022)
The ability of students in learning English is still lacking. This is because students have difficulty understanding the text in English. Students also have difficulty speaking English. The learning methods and media used by the teacher do not attract students' interest in learning English. With some of these problems, students are less and less interested in learning English and think that English is a difficult and boring subject. The purpose of this study is to analyze the types of difficulties in learning English experienced by students, and the factors that make students difficult to learn English. This research method used a qualitative descriptive approach. The research subjects wer